2014
DOI: 10.1111/ijsa.12082
|View full text |Cite
|
Sign up to set email alerts
|

Validity Evidence for a Croatian Version of the Conditional Reasoning Test for Aggression

Abstract: The Conditional Reasoning Test for Aggression (CRT‐A) is based on the idea that aggressive individuals use motive‐based cognitive biases to see their behavior as reasonable and that those biases can be measured with inductive reasoning tasks. Although the initial validation efforts for the CRT‐A in the United States have been reasonably successful, there has been no attempt to determine if the evidence of validity and reliability generalizes to other cultural contexts. In this paper, we describe four studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
(70 reference statements)
0
26
0
Order By: Relevance
“…The Croatian adaptation of the test was created after a careful adaptation process including the translation‐back translation procedure (see Galić et al ). The internal consistency of the CRT‐A in this study was 0.65…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Croatian adaptation of the test was created after a careful adaptation process including the translation‐back translation procedure (see Galić et al ). The internal consistency of the CRT‐A in this study was 0.65…”
Section: Methodsmentioning
confidence: 99%
“…LeBreton, Barksdale, Robin, and James (), and Galić et al () showed that the CRT‐A is resistant to faking when the indirect nature of the measurement is preserved, which is important for personnel selection researchers and practitioners. When respondents were instructed that they were solving a reasoning test, manipulation shown to induce faking using self‐report surveys (i.e., simulated personnel selection) did not produce changes in the CRT‐A scores.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, the only systematic evidence of the validity of the conditional reasoning assumptions in a context largely outside the US was recently published for the Croatian validation of the CRT-A (Galić, Scherer, & LeBreton, 2014). To the best of our knowledge, the only systematic evidence of the validity of the conditional reasoning assumptions in a context largely outside the US was recently published for the Croatian validation of the CRT-A (Galić, Scherer, & LeBreton, 2014).…”
Section: Prospects For Conditional Reasoning In Personality Assessmentmentioning
confidence: 99%